Pengaruh Informasi Akuntansi dan Ketidakpastian Tugas terhadap Kinerja Manajer - Efendi, David (Universitas Muhammadiyah Yogyakarta, Indonesia, 2007)
The different between the previous result of research about the influence of accounting information and task uncertainty of manager behavior provide an impulse to do the research with some modification. The research was done to cooperative because cooperative has roles and functions in the development of potency and economic capability to increase welfare of the members cooperative and society at large. This research was designed to examine and explain empirically about the influence of behavior accounting and management accounting. Besides it contributes for the cooperative about factor influence of manager performance and the impulse of research in this field management accounting in the future. Cooperative manager in the Madiun regency were used as unit analysis in this research. The sampling method with the clustered sampling use two stages. The data were collected directly with questioner was a week after questioners have been given. Method of analysis used in this research is simple regression for alternative hypothesis 1 and multiply regression for alternative hypothesis 2. The collected data is reliable while based on validity test there are many statement from task uncertainty and manager performance. The simples regression analysis show that accounting information has the positive influence of manager performance. And multiply regression analysis show that two variable independent influence to variable dependent, accounting Information has the positive influence and task uncertainty has negative influence of manager performance.